Clinical characteristics and follow-up of Korean patients with adrenal incidentalomas - Cho, Yoon Young (The Korean Association of Internal Medicine, 2013)
BACKGROUND/AIMS: We investigated the clinical characteristics and follow-up findings of subjects with adrenal incidentalomas in a single, tertiary-care hospital in South Korea. METHODS: The study consisted of a retrospective analysis of 282 adrenal incidentaloma patients who underwent radiographic and endocrinological evaluations at Samsung Medical Center in Seoul, South Korea, between January 2004 and July 2011. RESULTS: Most (86.2%) of the subjects were found to have nonfunctioning tumors. Functioning tumors were seen in 39 patients (13.8%). Among them, 28 (9.9%) had subclinical Cushing syndrome (SCS), six (2.1%) had pheochromocytoma, and five (1.8%) had primary hyperaldosteronism. Malignant adrenal tumors were discovered in three cases: two (0.7%) were primary adrenal cancers, and one (0.4%) was a secondary metastasis from a lung cancer. Significant risk factors for functional tumors were female gender (odds ratio [OR], 3.386; 95% confidence interval [CI], 1.611 to 7.117; p = 0.0013) and a noncontrast attenuation value of > 10 Hounsfield units (OR, 2.806; 95% CI, 1.231 to 6.397; p = 0.0141). During follow-up (mean, 22.5 months) of 72 of the patients, three (4.2%) developed hormonal changes due to functional tumors. One was confirmed as pheochromocytoma by histopathology, and the others were diagnosed with SCS and followed routinely without surgical intervention. No malignant transformation was found in these patients. CONCLUSIONS: Based on these findings, initial hormonal and radiographic evaluations for adrenal incidentalomas appear to be more important than follow-up tests because functional or malignant changes are rare.